The truth of a madman: the works of Art Spiegelman - Philip Smith (2014)
Art Spiegelman is one of the most important figures in the history of American comics. His work Maus (1980 and 1991) is arguably the landmark text in the field of comic book studies. Given the relatively recent reissue of his first collection Breakdowns (2008) and the publication of his interview/essay collection/scrapbook Metamaus (2011), it is likely that his work will continue to be the subject of critical interest. This thesis concerns the collections Breakdowns (1977 and 2008), Maus (1980 and 1991) and In the Shadow of No Towers (2004). It represents the first book-length extended study of Spiegelman s three major works. The central argument put forth in this thesis is that the Spiegelman oeuvre articulates and manifests a madness which its author perceives to underlie supposedly rational society. In support of this thesis I will employ critical models from the following fields: Holocaust studies, trauma theory, the anti-psychiatry movement, theories concerning the representation of madness, formalist analyses of comics, and Genette s narratological taxonomy.